2017
DOI: 10.4049/jimmunol.1601272
|View full text |Cite
|
Sign up to set email alerts
|

The STAT4/MLL1 Epigenetic Axis Regulates the Antimicrobial Functions of Murine Macrophages

Abstract: Macrophages are critical immune cells for the clearance of microbial pathogens and cellular debris from peripheral tissues. Macrophage inflammatory responses are governed by gene expression patterns, and these patterns are often subject to epigenetic control. Chromatin modifications such as histone methylation regulate gene accessibility in macrophages, and macrophage polarization is governed in part by the expression and function of chromatin modifying enzymes. The histone methyltransferase Mixed-Lineage Leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…We found significant increases in MLL1 in wound macrophages at days 3 and 5, suggesting that MLL1 plays an important role in regulating early macrophage-mediated wound inflammation. To determine whether this early increase in MLL1 in wound macrophages is necessary for healing, we used Mll1 +/− heterozygote mice ( Mll1 −/− are embryonically lethal) to determine whether wounds with decreased MLL1 had impaired early healing (21). We first confirmed that wounds isolated from the Mll1 +/− mice expressed less Mll1 transcript than littermate controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found significant increases in MLL1 in wound macrophages at days 3 and 5, suggesting that MLL1 plays an important role in regulating early macrophage-mediated wound inflammation. To determine whether this early increase in MLL1 in wound macrophages is necessary for healing, we used Mll1 +/− heterozygote mice ( Mll1 −/− are embryonically lethal) to determine whether wounds with decreased MLL1 had impaired early healing (21). We first confirmed that wounds isolated from the Mll1 +/− mice expressed less Mll1 transcript than littermate controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, H3K4me3 is controlled by the SET1-MLL family of enzymes (20). Although the role of MLL1 in oncogenesis has been investigated, few studies have examined the role of MLL1 in innate immunity (17,19,21). Furthermore, the function of MLL1 in normal physiology, particularly in wound healing, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The acquiescence of phenotypic stability by myeloid cells via epigenetic histone modification has been reported and is an area of intense investigation (2,18,41). The most recognized example is the phenomenon of "trained immunity," when myeloid cells (monocytes and macrophages) acquire properties compatible with immunological memory.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, H3K4me3 is controlled by the SET1/MLL family of enzymes (13). Although the role of MLL1 in oncogenesis has been investigated, few studies have examined the role of MLL1 in innate immunity (10,14,15). We have recently identified that MLL1 may regulate macrophage cytokine expression; however, the role of MLL1 in regulating upstream signaling pathways remains poorly defined (16).…”
mentioning
confidence: 99%